Bovine Herpesvirus 5 promotes mitochondrial dysfunction in cultured bovine monocyte-derived macrophages and not affect virus replication - Cardoso, Tereza C. [UNESP]; Okamura, Lucas H. [UNESP]; Baptistella, Jamila C. [UNESP]; Borsanelli, Ana Carolina [UNESP]; Baptistiolli, Lillian; Ferreira, Helena L.; Gameiro, Roberto [UNESP]; Flores, Eduardo F. (Elsevier, 2019)
Bovine alphaherpesvirus 1 (BHV1) and 5 (BHV5) are known to establish latent infections in sensory neurons of the trigeminal ganglion, yet leukocytes and tonsils have also been described as sites of latency in experimentally infected cattle. Little information is available on which immune cells are susceptible to BHV5 infection and how the infection may affect cell bioenergy. The aim of this study was to determine whether primary bovine monocyte-derived macrophages are susceptible to BHV5 infection and to evaluate parameters such as cell survival, virus replication and nitric oxide (NO) production. In addition, production of reactive oxygen species and mitochondrial damage were also analyzed. BHV5 infected cells underwent low rates of apoptosis but activated mitochondrial membrane depolarization and complex I. Additionally, production of high NO levels upon monocyte derived-macrophage infection did not interfere with the production of progeny virus. Overall, our findings revealed that primary cultures of bovine monocyte-derived macrophages support BHV5 replication in vitro and that mitochondrial dysfunction induced by infection apparently does not interfere with virus replication.
Keywords: BHV5; Cell bioenergy; Innate immune cells; Mitochondrion